{{ item.displayTitle }}

No history yet!

Student

Teacher

{{ item.displayTitle }}

{{ item.subject.displayTitle }}

{{ searchError }}

{{ courseTrack.displayTitle }} {{ statistics.percent }}% Sign in to view progress

{{ printedBook.courseTrack.name }} {{ printedBook.name }} In an arithmetic sequence, we find each term by adding the $common$ $difference$ to the previous term. For the given sequence, we need to subtract $6$ from the $first$ $term$ to find the second term. $18⟶−6 12… $ We can continue in the same way to find any number of terms in the sequence. Here we've been asked to find the three terms that come after the first term. This means that we will subtract $6$ from $18,$ three times. $18⟶−6 12⟶−6 6⟶−6 0 $ Therefore, the next three terms are: $12,$ $6,$ and $0.$